Vertical flow constructed wetlands subject to load variations: an improved design methodology connected to outlet quality objectives - Boutin, C.; Prost-Boucle, S. (Water science and technology, 2015)
This study surveyed four campsites and four rural villages of major tourist interest, called tourist-interest or ti-villages, that were monitored for several years, generating over 70 performance balances for vertical flow constructed wetlands (VFCWs) that were intentionally scaled down for experimental trials. The wastewater effectively qualifies as domestic sewage, although relatively concentrated, with the campsites presenting particularly high nitrogen concentrations (122 gTKN L–1) (TKN: total Kjeldahl nitrogen). The applied daily loads were also particularly high, with some combinations of load parameters (hydraulic load, organic matter, TKN) leading to 400% overloading. Even under those drastic conditions, the quality of effluent remained excellent on the characteristic organic matter parameters, with removal performances always over 85%. Analysis of the dataset points to two major design thresholds: for campsites, in order to maintain a 73% nitrification rate even at the height of the summer season, the load applied onto the first stage filter in operation could achieve up to 600 gCOD m–2 day–1 (COD: chemical oxygen demand). For tourist-interest villages, in order to maintain an 85% nitrification rate, the load applied onto the second stage filter in operation could achieve up to 22 gTKN m–2.day–1. Here, VFCWs were demonstrated to robustly handle a massive increase in loads applied, providing the construction and operation stringently follow design standards and practices.